2007
DOI: 10.2334/josnusd.49.293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylitol and fluoride on enamel erosion in vitro

Abstract: This study aimed to determine the anti-erosive effects of xylitol, fluoride and a xylitol/fluoride combination used as an additive in an acidic drink or as mouthrinse after enamel was exposed to an acidic drink, in vitro. Human third molars were divided into 7 groups (A-G). Samples from groups A to D were immersed for 5 min in orange juice only (A), orange juice plus either 25% xylitol (B), F(-) 1 ppm (C) or a 25% xylitol/F(-) 1 ppm combination (D), respectively. Samples from groups E to G were immersed in ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 23 publications
2
37
2
4
Order By: Relevance
“…The results of the present study agree with Souza et al 29 who concluded that xylitol had a significant remineralization potential after acid attacks as revealed by SEM results while it disagreed with the results of the study by Chunmuang et al 30 that conclude that various protective agents including 40% xylitol was unable to reduce tooth surface and mineral loss due to acid attacks (orange juice). This might be due to the difference in the erosive protocol as they used successive erosive challenges which might have limited the protective and remineralizing effects of the agents used.…”
Section: Discussioncontrasting
confidence: 50%
“…The results of the present study agree with Souza et al 29 who concluded that xylitol had a significant remineralization potential after acid attacks as revealed by SEM results while it disagreed with the results of the study by Chunmuang et al 30 that conclude that various protective agents including 40% xylitol was unable to reduce tooth surface and mineral loss due to acid attacks (orange juice). This might be due to the difference in the erosive protocol as they used successive erosive challenges which might have limited the protective and remineralizing effects of the agents used.…”
Section: Discussioncontrasting
confidence: 50%
“…Anneroth et al, (46) reported that the use of chewing gums can cause similar bad effects. In order to avoid demineralising effect on the human dentin, the use of spray format allows a direct contact with the oral mucosa, and combined with a suitable concentration (as the stimulant effect on saliva production), could reduce the demineralising potential of chewable products (47,48). da Mata et al, (49) indicated that Gustatory stimulants of salivary secretion with fluoride, xylitol and lower acid content maintain similar salivary stimulation capacity while reducing significantly the dental erosion predictive potential.…”
Section: Management Of Dry Mouthmentioning
confidence: 99%
“…The resultant maps may be compared using a surface matching and difference detection algorithm. This technique provides readings with good accuracy and reproducibility [60][61][62] [ [43][44][45]. Erosions of 50 tJm magnitude occurring over a 9 month period were recorded to a precision of about ±15 tJm [59] [42].…”
Section: Surface Profilometrymentioning
confidence: 99%